Migration Trajectories among Rural Households in Indonesia - Agus Joko Pitoyo; Idris Ihwanudin; Sukamdi Sukamdi; Muhammad Arif Fahrudin Alfana; Seri Aryati (Indonesian Journal of Geography, 2022)
International migration trajectory is one of the important aspects discussed when viewing the migration culture of a region. The specific types and patterns created are unique and dependent on the length of the migration history. Therefore, this study is aimed to explain the migration history carried out by residents in Ponorogo Regency, East Java Province, and the factors that influence international migration. This is a survey research of 515 international migrants. The results showed that the migration pattern in Ponorogo Regency was divided into one, two, and three destination countries with temporal space-related cultural factors used to determine an important influence on rural households' ability to work abroad. Similar to other studies, age and gender are the two key variables related to migration trajectories in Ponorogo Regency.